2006
DOI: 10.1387/ijdb.052072hb
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human embryonic stem cells into hepatocytes in 2D and 3D culture systems in vitro

Abstract: Human embryonic stem cells (hESCs) have enormous potential as a source of cells for cell replacement therapies and as a model for early human development. In this study we examined the differentiating potential of hESCs into hepatocytes in two-and three-dimensional (2D and 3D) culture systems. Embryoid bodies (EBs) were inserted into a collagen scaffold 3D culture system or cultured on collagen-coated dishes and stimulated with exogenous growth factors to induce hepatic histogenesis. Immunofluorescence analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
268
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(278 citation statements)
references
References 27 publications
4
268
1
5
Order By: Relevance
“…The liver is a good objective for studying tissue stem cell differentiation into tumor tissue cells in vitro [55], since several stem cells lines can differentiate and regenerate into functional liver cells [59] , and effective hepatic differentiation protocols have already been established [49][50][51][52][53]60]. It has also been demonstrated that the in vitro produced hepatocyte-like cells transplanted into patients can differentiate into functional liver cells [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is a good objective for studying tissue stem cell differentiation into tumor tissue cells in vitro [55], since several stem cells lines can differentiate and regenerate into functional liver cells [59] , and effective hepatic differentiation protocols have already been established [49][50][51][52][53]60]. It has also been demonstrated that the in vitro produced hepatocyte-like cells transplanted into patients can differentiate into functional liver cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, HUES1 and HUES9 as human embryonic stem cell lines were used. There are a number of models, based on which human embryonic stem cell lines are differentiated into hepatic direction [51,53,60]. The differentiation protocol applied in our study is straight forward and characterized with well-defined differentiation stages [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…It was not until 2000-2010, however, that one began to see more and more researches in this emerging field. This is when many of the pioneers in TE research began to make their mark [15][16][17][18]. It is important to consider that the focus of Iranian researchers was on engineering bone and nerve tissue, by an integrated use of stem cells and biomaterial scaffolds.…”
Section: To Presentmentioning
confidence: 99%
“…Results revealed that the differentiated cells give rise to cells displaying morphological features, gene expression patterns, and metabolic activities characteristic of hepatocytes. Authors proposed that hESCs may provide a source of differentiated cells for treatment of liver diseases [15].…”
Section: Embryonic Stem (Es) Cellsmentioning
confidence: 99%
“…[9][10][11] The 3D structure of EBs promotes differentiation more efficiently than cells in 2D and is proposed to be the mechanism underlying this phenomenon. 12 Sequential stimulation with growth factors and introduction of growth factors promotes human iPS cells to produce hepatocyte-like cells. [13][14][15][16] EBs that express the genes necessary for differentiation would be expected to differentiate more efficiently.…”
Section: Introductionmentioning
confidence: 99%